AN ECOFEMINIST STUDY OF FAHMIDA RIAZ’S SELECTED POEMS TRANSLATED BY TAHIRA NAQVI (Contemporary Journal of Social Science Review, 2025)
This research examines eco-feminist themes in the poetry of Fahmida Riaz, using a qualitative research method. This study explores the intersection of ecofeminist concerns with Riaz’s poetry through a detailed analysis of selected poems. The study focuses on how Riaz’s work embodies ecofeminist principles by examining themes such as women’s oppression, exploitation of the land and the search for liberation. Riaz’s work reveals recurring themes and symbols in her poetry, such as natural themes and gender imagery, and places them in the larger context of her time. Using an ecofeminist theoretical framework, the thematic analysis approach demonstrates how Riaz’s poetry challenges patriarchal structures and presents a perspective of resistance and renewal. The findings show that Riaz’s poetry not only expresses its cultural content but also supports ecofeminist discourse by demonstrating the interaction between genders, human and environmental justice. The study uncovers how Riaz uses poetic expression to challenge both cultural and environmental injustices, giving voice to the marginalized both women and nature. Her poetry emerges as a site of resistance, critique, and transformation, offering alternative ways of understanding the relationship between women, nature, and power structures. It contributes to the understanding of ecofeminism in South Asian literature and provides insight into how literature engages with and challenges key concepts such as power and control. This study highlights the importance of Riaz's poetry in promoting ecofeminist critique and argues for recognition of her contribution to literature and feminism.